Proceedings of the International Scientific and Practical Conference on Education, Health and Human Wellbeing (ICEDER 2019) 2020
DOI: 10.2991/iceder-19.2020.8
|View full text |Cite
|
Sign up to set email alerts
|

The School Innovative Educational Model: Issues of Digitalization

Abstract: The purpose of the study is to build an innovative educational model of a digital school based on an analysis of the best practices in using digital technologies in the educational activities of the school. The study analyzes the practical experience of the leading schools of Russia implementing various digitalization projects at their educational sites. The main results of the study characterize the components of the digital school model in the (a) targets, (b) software and technology, (c) content-methodologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Konsep digitalisasi menurut Yoo et al (2010) sebagai transformasi struktur dan hubungan sosio-teknis yang terjadi saat berpindah dari artefak non-digital hingga artefak digital. Digitalisasi pengelolaan sekolah adalah pengelolaan sekolah yang bersifat modern, otomasi pekerjaan-pekerjaan divisi sekolah dan penyediaan akses ke teknologi modern (Boronenko et al, 2020). Di banyak sekolah, penerapan teknologi digital sudah banyak dilakukan untuk belajar mengajar (Zheng et al, 2016).…”
Section: Digitalisasi Pengelolaan Sekolahunclassified
“…Konsep digitalisasi menurut Yoo et al (2010) sebagai transformasi struktur dan hubungan sosio-teknis yang terjadi saat berpindah dari artefak non-digital hingga artefak digital. Digitalisasi pengelolaan sekolah adalah pengelolaan sekolah yang bersifat modern, otomasi pekerjaan-pekerjaan divisi sekolah dan penyediaan akses ke teknologi modern (Boronenko et al, 2020). Di banyak sekolah, penerapan teknologi digital sudah banyak dilakukan untuk belajar mengajar (Zheng et al, 2016).…”
Section: Digitalisasi Pengelolaan Sekolahunclassified
“…Additionally, Håkansson Lindqvist & Pettersson's [3] reported that school leaders understand digitization and the digital competencies by setting the direction, developing human resources, developing organizations, and developing teachinglearning. The research of T. Boronenko et al [6] and Liisa Ilomäki et al [7] stated that school digitization includes (a) creating an electronic digital school management system, (b) creating innovative electronic information files and educational environments; (c) implementing the education network program; (d) developing the digital competence of teachers and students.…”
Section: Introductionmentioning
confidence: 99%